3D Inversion of Gravity Data Modeling Using The Chi Fact Algorithm for Revealing Subsurface Structure in Semarang City - Rina Dwi Indriana; Mochamad Aryono Adhi; Danastri L. P. Tampubolon; Sorja Koesuma (Department of Physics, Sebelas Maret University, 2022)
The interpretation of subsurface in the Semarang City with 3D inversion model using the Chi Fact algorithm has been carried out to reveal the subsurface especially related to the presence of groundwater basins. The gravity data model in this research uses 80 stations with a research area of 20 km2 which is specialized in the surrounding area of Kaligarang district. The results of the 3D inversion using the Chi Fact algorithm founded the distribution of subsurface rock density values in the Semarang City area ranging from 1.6 gr/cc to 2.98 gr/cc. The distribution of subsurface density values indicates the subsurface geological structure of the Semarang City area had a normal fault leading to the southeast.